Belgrade housing modernisation in the first half of 20th century – transformation of spatial concept, construction and materialization of multy-story residential buildings - Roter Blagojević, Mirjana; Đukanović, Ljiljana (Arhitektura i urbanizam, 2020)
Multi-storey business-residential and residential buildings have been increasingly present in Belgrade since 1900 and testify to its accelerated modernization. In the period before the First World War, the basic types of multi-family residential buildings were developed and characteristic forms of building assemblies and spatial organization of apartments were formed. As builders were educated in Central European centres (Pest, Vienna, Munich, Aachen, Berlin and Zurich), the types of assemblies and apartments were created according to their influence. After the war, in addition to the old, the younger generation of architects educated at the Architectural Department of the Technical Faculty in Belgrade is also active, which contributes to a greater variety of solutions and the influence of long European centres (Prague and Paris). Through the analysis, examples from the period 1900-1914 are considered and compared. and 1918-1941. in order to define the basic types of building shapes, assemblies and spatial organization of apartments. The aim of the research is to confirm the thesis on the continuity of development and application of the same basic types of buildings and spatial organization of apartments in both periods. The thesis of continuous use of masonry construction for making walls in both periods was also confirmed, while the use of modern material, reinforced concrete, and semi-prefabricated Herbst construction became established during the third and fourth decades of the 20th century.